2017
DOI: 10.1177/1362361317710798
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of parent recall of symptom onset and timing in autism spectrum disorder

Abstract: Past events are often reported as occurring more recently than they actually took place, an error called forward telescoping. This study examined whether forward telescoping was evident in parent reports of ASD symptom emergence and onset classification. Parents were interviewed when their child was 2–3 years old (Time 1) and approximately 6 years old (Time 2). Significant forward telescoping was found in both age of social regression and age when language milestones were achieved, but not age of language regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
(51 reference statements)
2
19
1
Order By: Relevance
“…Agreement was markedly lower when ratings were retrospective or categorical or both. This suggests that the discrepancies previously identified between parent report of regression and other indices [Ozonoff et al, ] are due to multiple factors, both the way the question is asked (categorical vs. dimensional) and when it is asked (concurrently or in retrospect). Similarly, studies of other disorders have converged on the conclusion that reports of psychopathology are much more likely when measured prospectively than retrospectively [Moffitt et al, ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Agreement was markedly lower when ratings were retrospective or categorical or both. This suggests that the discrepancies previously identified between parent report of regression and other indices [Ozonoff et al, ] are due to multiple factors, both the way the question is asked (categorical vs. dimensional) and when it is asked (concurrently or in retrospect). Similarly, studies of other disorders have converged on the conclusion that reports of psychopathology are much more likely when measured prospectively than retrospectively [Moffitt et al, ].…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have documented the ways in which recall problems and other biases can influence parent report. For example, several studies have demonstrated changes in recall over time, with parents less likely to report regression and more likely to report early delays as their children grow older (Hus et al, 2011; Lord et al, 2004; Ozonoff et al, in press). In a study that compared classification of onset based on objective coding of family movies to onset type as recalled by parents (Ozonoff et al, 2011), less than half of children whose home video displayed clear evidence of a major decline in social-communication behavior were reported to have had a regression by parents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, temporary loss of ambulation because of an acute seizure or decreased attentiveness and discomfort from severe constipation could easily bias clinical assessments for the day. Retrospective parental reporting of a patient's functioning is thus required to fill in the gaps; however, the long intervals of reporting common to the design of natural history studies to minimally inconvenience families creates significant potential for recall bias . Future efforts employing modern technologies for remote observational data collection and parental reporting through ecological momentary assessment strategies could permit more frequent and timely assessments of patients in their home environment; thus, helping to minimize the burden of travel while more fully ascertaining the spectrum of severity in neurodevelopmental disorders such as MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding reports of symptom onset, parents of older children seem to report later ages of regression onset (Barger et al, 2013;Lord et al, 2004) and Tuchman and Rapin (1997) found that parents of younger children are more likely to report regression compared to parents of older children. In a recent prospective longitudinal study by Ozonoff, Li, Deprey, Hanzel, & Iosif (2018) change in onset classification was associated with parents not recalling a regression at the second visit that they had reported when interviewed earlier at the first visit. In a study by Jones et al (2015) it was also found that timing of consecutive interview questions impacts responses of caregivers, namely, when information on history of symptoms was asked first, less severe past and current behavior was reported compared to caregivers reporting current and history of symptoms together.…”
Section: A Loss Supplementmentioning
confidence: 93%